Correlation Study of Shrinkage Expansion Potential of Clay Soil In PLTMH Cileunca, Pangalengan, Bandung, Indonesia - Kurniawan, Indra Fajar; Maulana, Ahmad Rizky Ananda; Naufal, Muhammad Faris; Rezeki, Ingrid Multi (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
Mini Hydro Power Plants (MHPs) utilize the potential of water to generate electrical energy. However, construction on clay soils that have the potential to expand and contract can affect the stability of the structure. This study aims to evaluate the potential for soil development in the Cileunca MHP. The methods used to determine soil development potential include Chen (1988), Skempton (1953), and Seeds (1962) methods. Mineral identification was conducted through X-Ray Diffraction (XRD) testing of soil samples taken by the handboring method. The results of the analysis showed that the Skempton method showed 67% of the samples had activity values > 0.75 (“high” category). The Chen method indicated 60% of the samples had a plasticity index (PI) > 35% (“very high” category). The Seeds method indicated 73% of the samples had a development potential > 25% (very high category). XRD testing indicated the dominant mineral was dehydrated Halloysite (Al2Si5(OH)4). The soil at the Cileunca MHP site has a high development potential that can damage building foundations. Foundation stability is strongly influenced by expansive soil properties, so soil stabilization treatment is needed to prevent structural damage. This study concludes that the soil at the Cileunca MHP site has a high development potential, which can cause structural problems. Therefore, soil stabilization treatment is highly recommended to ensure the stability of the building foundation